RESEARCH ON THE BACKGROUND INFLUENCE ON THE RESOLUTION AND DEFININITION OF THE VARIATIONS OF THE BACKGROUND LUMINANCE OF ELECTRONIC-OPTIC CONVERTERS: RESEARCH ON THE BACKGROUND INFLUENCE ON THE RESOLUTION AND DEFININITION OF THE VARIATIONS OF THE BACKGROUND LUMINANCE OF ELECTRONIC-OPTIC CONVERTERS - Getzov, Petar; Stoanov, Stiliyan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The urrent research refers to electronic-optical devices working in conditions of different levels of background luminance. The aim of the research is to define the influence of the background luminance upon the resolution of different types of electronic-optical converters. The aim is achieved by experimental research and dispersion analysis when mathematically processing the received data. A possibility to select the converters has been created according to the direct aspect of their usage. Four types of electronic-optical converters are used for official use and this is the reason why their technical characteristics are not presented.